The Influence Of Price And Service Quality On The Purchase Decision Of Pilgrims Choosing Pt Haji Mabrur Barokah In Pontianak - Destafariza, Feby Elfira; Triana M, Neni (UNIVERSITAS PAKUAN, 2024)
This study aims to analyze the influence of price and service quality on the purchase decisions of pilgrims who choose PT Haji Mabrur Barokah in Pontianak. The research method employed is quantitative with an associative approach, where data were collected through questionnaires distributed to 100 respondents. The results indicate that all research instruments are valid and reliable, and the data distribution is normal. The linearity test shows a linear relationship between price and service quality on purchase decisions. The multiple linear regression analysis reveals that both price and service quality have a positive and significant impact on purchase decisions, with regression coefficients of 0.162 for price and 0.480 for service quality. The F-test shows that both variables simultaneously have a significant effect on purchase decisions, while the t-test indicates a significant effect of each variable partially. The coefficient of determination of 39.1% indicates that price and service quality can explain the effect on purchase decisions, while the remaining percentage is influenced by other factors.